Transfer time of the MDP and its effect on the time-dependent lateral deformation capacity of coastal bridge piers. (December 2021) - Cheng, Hu; Wang, Dong-Sheng; Li, Hong-Nan; Yan, Xin-Chi; Yu, She
Abstract: In the maritime environment, the persistent attack of chloride ions will induce degradations of structural performance. Because of the surrounding exposure conditions, coastal bridge piers usually undergo discrepant deteriorations along the height, causing the maximum damaged position (MDP) to transfer from the conventional pier bottom to the zone that corroded most seriously. This study presents an analytical method to forecast the transfer time of the MDP for coastal bridge piers. The relationship between the structural capacity and seismic demand of the bottom section in each zone is monitored synchronously, aiming to capture the time and place that the structural capacity is first exceeded by the seismic demand. Next, an illustrative example of coastal bridge piers is adopted to demonstrate the proposed approach. The time-dependent lateral deformation capacity of the coastal bridge pier is investigated by considering the effect of the transfer time of the MDP. The analytical results show that the ultimate drift ratio of coastal bridge piers increases firstly and then, decreases significantly when the discrepant corrosion damages along the pier height is considered. As for the conventional simplified corrosion mode, i.e., using an equivalent mean corrosion level to describe the corrosion level for the global bridge pier, it cannot be adopted to estimate the actual time-dependent seismic performance of coastal bridge piers corroded non-uniformly along the height.